Causes and Consequences of Bullying Phenomenon among Emerging Adults in Urban Surabaya - Lisuallo, Damayanti; Hadinata, Desyria Anggraini; Gloryana, Gavrila; Silitonga, Bunga Meiuliwati; Theodora, Evonne; Yudiarso, Ananta (Journal of Urban Sociology, 2025)
The phenomenon of bullying among emerging adults has become an important research topic due to its significant impact on emerging adults' well-being and their learning environment. This research is crucial to understanding the root causes and triggering factors of bullying. By understanding the causes, more effective prevention measures can be designed and implemented by the government to create a safer and more supportive environment for emerging adulthood. The phenomenon of bullying can be explained through the perspectives of psychology, sociology and anthropology. This research is a qualitative study using the interview method. The results showed that from a psychological perspective, imitation of aggressive behavior from the social environment is the root of the bullying problem. From a sociology perspective, bullying is the result of power inequality and attempts to maintain power. From an anthropological perspective, cultural norms and social hierarchy influence bullying, which is used to maintain distance between dominant and perceived different groups.Keywords: bullyings; psychological; sociological; anthropological.